GRAMMATICAL ERROR ANALYSIS ON THE SPONTANEOUS SPEECH PRODUCED BY STUDENTS OF ENGLISH - SASTRA, LUSI VERA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Sastra, Lusi Vera.  (2014).  Grammatical Error Analysis on the Spontaneous Speech Produced by Students of English. English Study Program, Department of Languages  and Literature,  Faculty of Cultural  Studies, Universitas Brawijaya. Supervisor: Endang Sasanti Co-supervisor: Tantri Refa Indhiarti.Keywords: error analysis, error, speech, types of error.Language plays a very important role in communication. One of the languages that are mostly used in this world is English. English spreads globally because it has empowerment and imperialism in the past, which brought English all over the world to be an international language. In Indonesia,  English becomes  a compulsory and Indonesians are  required  learning  English through education system policy. In the process of learning, Indonesian students surely make errors. It is understandable since the rule of Bahasa Indonesia and English is different. This research aims, first,  to identify the types of errors and second, to find the most frequent error in the students’ speech  produced by the seventh semester students  of English Study Program of Universitas Brawijaya.  This research was  designed  by using descriptive qualitative approach and document analysis to answer the problem of the study. The data were collected from the transcript of thirty students’ speech which contains errors produced by the seventh semester students of Study Program of English Universias Brawijaya. In collecting the data, the researcher selected the participants who got good grade minimum B and above  in their structure  class and then asked  them to give spontaneous speech in limited time minimally one minute with the topics that have given by the researcher. The researcher analyzed the data by using the theory of Surface Strategy Taxonomy proposed by Dulay, Burt, and Krashen (1982).  The  results of this research showed  that the students made  some types of errors when they produce their speech. Those errors are omission  (37%), addition (27%), misformation  (35%)  and misordering  (1%). Omission was divided into  five types, addition into six types, misformation into six types and the last is misordering.  The researcher suggests the next researchers who want to conduct the similar research uses the different object and analyze the errors with other theories. Another suggestion is to use the similar theory but with different object.